Employing Orange Peel Residue to Produce Eco-Enzymes - , Sharif Rahmad Ali (Community Service Akseprin Journal, 2024)
Indonesia's substantial population, coupled with a rapid growth rate, has led to a rise in garbage generation, with the capital city producing 3.1 million tons of waste in 2023, predominantly consisting of organic waste. In 2023, East Jakarta generated the highest trash volume, totaling 844,252 tons annually. This is undoubtedly a responsibility for all stakeholders, from the government level to the family level. One initiative to diminish waste volume involves converting it into new goods, such as eco-enzymes. The community empowerment method, implemented through training, constitutes a public education initiative in waste management aimed at addressing the issue of organic waste. The training occurred in May 2023. The service results indicate that the training on eco-enzyme production in Pinang Ranti Village, aimed at utilizing household organic waste, was successful, yielding orange peel eco-enzyme products. The community exhibited considerable enthusiasm throughout the activities, and participants subsequently felt motivated to process organic waste. This activity is anticipated to be conducted continually and consistently by relevant stakeholders, particularly the government at both national and local levels